A liquid crystal of ascorbyl palmitate, used as vaccine platform, provides sustained release of antigen and has intrinsic pro-inflammatory and adjuvant activities which are dependent on MyD88 adaptor protein - Sánchez Vallecillo, María Fernanda (2015)
Modern subunit vaccines require the development of new adjuvant strategies. Recently,32 we showed that CpG-ODN formulated with a liquid crystal nanostructure formed by self33assembly of 6-O-ascorbyl palmitate (Coa-ASC16) is an attractive system for promoting an34 antigen-specific immune response to weak antigens. Here, we showed that after35 subcutaneous injection of mice with near-infrared fluorescent dye-labeled OVA antigen36 formulated with Coa-ASC16, the dye-OVA was retained at the injection site for a longer37 period than when soluble dye-OVA was administered. Coa-ASC16 alone elicited a local38 inflammation, but how this material triggers this response has not been described yet.39 Although it is known that some materials used as a platform are not immunologically inert,40 very few studies have directly focused on this topic. In this study, we explored the41 underlying mechanisms concerning the interaction between Coa-ASC16 and the immune42 system and we found that the whole inflammatory response elicited by Coa-ASC1643 (leukocyte recruitment and IL-1β, IL-6 and IL-12 production) was dependent on the MyD8844 protein. TLR2, TLR4, TLR7 and NLRP3-inflammasome signaling were not required for45 induction of this inflammatory response. Coa-ASC16 induced local release of self-DNA,46 and in TLR9-deficient mice IL-6 production was absent. In addition, Coa-ASC16 revealed47 an intrinsic adjuvant activity which was affected by MyD88 and IL-6 absence. Taken48 together these results indicate that Coa-ASC16 used as a vaccine platform is effective due49 to the combination of the controlled release of antigen and its intrinsic pro-inflammatory50 activity. Understanding how Coa-ASC16 works might have significant implications for51 rational vaccine design.